Analysis of the Level of Assertive Behavior among 9th Grade Students in Vocational High School - Assalam, Jian; Rakhmawati, Dini; Gunawan, Singgih (IKIP Siliwangi, 2024)
English: Assertive behavior is a person's ability to communicate in an equal relationship through feelings, opinions, thoughts and ideas directly, openly, without feelings of anxiety, being firm in rejecting requests that are unclear while still respecting the rights of others and being able to communicate with everyone. People without hurting their feelings. This background was carried out by the author because there was low assertive behavior in students. The aim of the research is for researchers to determine the level of assertive behavior in class XI students at SMK Negeri 7 Semarang. This research takes a quantitative approach using the scale method. In this study, we used a probability sampling strategy based on simple random sampling to select 138 class XI students. Research on the level of assertive behavior of class XI students at SMK Negeri 7 Semarang showed an average of 58% of These students are in the medium category, while 19% are in the low category and 24% are in the high category. Indonesia: Perilaku asertivitas merupakan suatu kemampuan seseorang berkomunikasi dalam hubungan yang setara melalui perasaan, pendapat, pemikiran serta gagasan secara langsung, terbuka, tanpa perasaan cemas, bersikap tegas dalam menolak permintaan yang sekiranya tidak jelas dengan tetap menghargai hak-hak orang lain serta dapat berkomunikasi dengan semua orang tanpa menyakiti perasaanya. Latar belakang ini di lakukan penulis dikarenakan terdapat perilaku asertivitas yang rendah pada siswa. Tujuan dari penelitian yaitu agar peneliti mengetahui tingkat perilaku asertivitas pada siswa kelas XI di SMK Negeri 7 Semarang. Penelitian ini mengambil pendekatan kuantitatif dengan menggunakan metode skala. Dalam penelitian ini, kami menggunakan strategi pengambilan sampel probabilitas berdasarkan simple random sampling untuk memilih 142 siswa kelas XI. Penelitian mengenai tingkat perilaku asertif siswa kelas XI di SMK Negeri 7 Semarang menunjukkan rata-rata 58% siswa tersebut masuk dalam kategori sedang, sedangkan 19% berada pada kategori rendah dan 24% berada pada kategori tinggi.